Writing Skill’ Assessment of English Department’ Fourth Semester Students at University of HKBP Nommensen Pematangsiantar (UHKBPNP) - Leonita Maria Efipanias Manihuruk; Berlin Sibarani; M Meisuri (PT Inovasi Pratama Internasional, 2024)
The objective of this research is to assess how the writing skill’ of the Department students at University of HKBP Nommensen Pematangsiantar (UHKBPNP). The subject of this research is 4th semester students of UHKBPNP, with consist of 25 students. The research design of this research is qualitative approach with case study method. The instrument of collecting data used is writing test. The findings of the research: (1) Content aspect score was 14.88; (2) Organization aspect score was 12.32; (3) Vocabulary aspect score was 14.8; (4) Language use aspect score was 14.48; (5) Mechanics aspect score was 13.88. The result of the research showed that the students experienced mostly in excellent to very good level.